Saturn's Nightside Ring Current During Cassini's Grand Finale. Issue 3 (8th March 2021) - Provan, G.; Bradley, T. J.; Bunce, E. J.; Cowley, S. W. H.; Cao, H.; Dougherty, M.; Hunt, G. J.; Roussos, E.; Staniland, N. R.; Tao, C.
Abstract: During Cassini's Grand Finale proximal orbits, the spacecraft traversed the nightside magnetotail to ∼21 Saturn radii. Clear signatures of Saturn's equatorial current sheet are observed in the magnetic field data. An axisymmetric model of the ring current is fitted to these data, amended to take into account the tilt of the current layer by solar wind forcing, its teardrop‐shaped nature and the magnetotail and magnetopause fringing fields. Variations in ring current parameters are examined in relation to external driving of the magnetosphere by the solar wind and internal driving by the two planetary period oscillations (PPOs), and compared with previous dawn and dayside observations. We find that the relative phasing of the PPOs determines the ring current's response to solar wind conditions. During solar wind compressions when the PPOs are in antiphase, a thick partial ring current is formed on the nightside, dominated by hot plasma injected by tail reconnection. This partial ring current should close partly via magnetopause currents and possibly via field‐aligned currents into the ionosphere. However, during solar wind compressions when the PPOs are in phase, this partial ring current is not detected. During solar wind rarefactions an equatorial "magnetodisc" configuration is observed in the dayside/dawn/nightside regions, with similar total currents flowing at these local times. During very quiet intervals of prolonged solar wind rarefaction, a thin current sheet with an enhanced current density is formed, indicative of a ring current dominated by cool, dense, Enceladus water group ions. Plain Language Summary: We have studied Saturn's nightside ring current during Cassini's Grand Finale. We find that Saturn's ring current, like Saturn's magnetosphere as a whole, is driven by factors both internal and external to the magnetosphere. The external driver is the solar wind and the internal drivers are the planetary period oscillations. Magnetospheric storms, triggered by both drivers, result in a partial ring current of hot plasma on Saturn's nightside. Key points: We study Saturn's nightside ring current during Cassini's Grand Finale Saturn's nightside ring current is driven jointly by the external solar wind and by the internal planetary period oscillations Magnetospheric storms, triggered by both the internal and external drivers, result in a partial ring current of hot plasma on the nightside